CATCALLING DALAM PERSPEKTIF HUKUM PIDANA: SUATU TINJAUAN TERHADAP PELECEHAN VERBAL DI RUANG PUBLIK - Jamaludin, Jamaludin; Ramdani Abd. Hafizh, Ramdani Abd. Hafizh; Tata Eliestiana Dyah A, Tata Eliestiana Dyah A (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2024)
Abstract Sexual harassment in public spaces, particularly in the form of catcalling, is a common occurrence but is often considered trivial. However, these sexually charged verbal acts have the potential to demean the victim and have serious consequences, necessitating clear boundaries and assessments from a criminal law perspective in Indonesia. This study aims to analyze the definition and boundaries of catcalling as a form of verbal sexual harassment in public spaces from a criminal law perspective in Indonesia and to examine its impact on victims. This study uses a normative legal research method with a statutory, conceptual, and case-based approach. The legal materials used include primary, secondary, and tertiary legal materials collected through literature review. The legal materials were analyzed using legal interpretation methods. The results of the study indicate that catcalling is a form of verbal sexual harassment that contains unwanted elements, is sexually oriented, and demeans the victim's dignity, so it can be qualified as a crime against morality that is contrary to the values ​​of human rights protection and the principle of victim protection in criminal law. The limitations of catcalling as verbal harassment in public spaces include the presence of unwanted remarks or gestures, carried out in public spaces, and causing a feeling of insecurity for the victim. In addition, catcalling has a multidimensional impact on the victim, both psychologically in the form of trauma, fear, and mental health disorders, socially in the form of anxiety, restricted movement, and decreased self-confidence, as well as economically which affects productivity, opportunities for social mobility, and increased expenditure on the victim's needs.